Perspectives on Constructivism in Indonesian Diplomacy in the Indo-Pacific Economic Framework - Leonard Felix Hutabarat (Jurnal Hubungan Internasional, 2024)
This article explains how Indonesia responded to United States President Joe Biden's initiative in establishing the Indo-Pacific Economic Framework on May 23, 2022. Indo-Pacific terminology grows out of regional geopolitical constructs to accommodate international security and political interests. Various connectivity strategies have divided the interests of different countries in initiatives to cooperate. The need for countries in the Indo-Pacific region to collaborate must be a shared priority, especially in preventing polarization in the region and minimizing open conflict between superpowers and their allies. Geopolitical and geostrategic aspects must be addressed rationally by Indonesia. This article is useful for stakeholders in Indonesia in looking at United States initiatives in a broader range of interest dimensions. Indonesia's foreign policy and diplomacy towards the Indo-Pacific Economic Framework can be seen from the perspective of constructivism in the study of international relations. This study is based on a qualitative method by explaining the related interests of the pillars that the United States offers in the Indo-Pacific Economic Framework. Based on Indonesia's national interests, diplomacy is strategic in an effort to balance the interests of economic cooperation between the United States and the People's Republic of China, involvement in the formation of policy frameworks and norms setting or cooperative mechanisms  for developing countries in the region, as well as efforts to fight for the interests of ASEAN centrality in accordance with the ASEAN Outlook on Indo-Pacific.